1996
DOI: 10.1016/0014-5793(96)00266-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor, but not hepatocyte growth factor, suppresses the apoptosis induced by transforming growth factor‐beta in fetal hepatocytes in primary culture

Abstract: We studied whether the TGF-~-induced apoptosis in fetal hepatocyte primary cultures may be modulated by the presence of mitogenic stimuli, such as EGF or HGF. EGF prevented cell death, showing a dose dependence that was identical to that observed for its effect on DNA synthesis stimulation. HGF, in contrast, had no effect, even at high concentrations. EGF blocked apoptosis, since in the presence of this factor cells did not show DNA fragmentation. Moreover, EGF, but not HGF, blocked c-fos induction associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 31 publications
6
52
0
Order By: Relevance
“…As seen in fig. 2D [25,26], our data support a critical role for EGFR in protecting against TGF-β-induced apoptosis in oval cells. (Fig.…”
Section: Oval Cells Express Egfrsupporting
confidence: 64%
See 1 more Smart Citation
“…As seen in fig. 2D [25,26], our data support a critical role for EGFR in protecting against TGF-β-induced apoptosis in oval cells. (Fig.…”
Section: Oval Cells Express Egfrsupporting
confidence: 64%
“…Indeed, we and others have previously reported that EGF induces proliferation [20] and protects hepatocytes from various apoptotic insults, including TGF-β, Fas, and deoxycholic acid [25,35,36].…”
Section: It Is Well Known That Egfr-dependent Signalling Integrates Pmentioning
confidence: 75%
“…However, the role of EGF in the promotion of cell survival has only been reported in a limited number of cases. For example, EGF suppresses apoptosis induced by transforming growth factor b (TGFb) in primary hepatocytes (Fabregat et al, 1996). In mammary epithelial cells, apoptosis induced by a combination of serum-free medium and high cell density is prevented by EGF (Merlo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, growth factors may also contribute towards cell survival since growth factor withdrawal can lead to apoptosis (Oltvai et al, 1993;White 1996). There are numerous examples demonstrating that EGF can prevent apoptosis in response to a wide variety of stimuli (Coles et al, 1993;Luciano et al, 1994;Nakajima et al, 1994;Fabregat et al, 1996;Garcia-Lloret et al, 1996), and inhibition of EGFR expression can induce apoptosis (Englert et al, 1995). Since activation of EGFRs may be involved in stimulating colonic epithelium proliferation and in antagonizing apoptosis, one potential mechanism to suppress colorectal cancer may include modulation of apoptotic pathway(s) by inhibiting EGFR using anti-EGFR mAbs.…”
mentioning
confidence: 99%